2016
DOI: 10.1097/hjh.0000000000000852
|View full text |Cite
|
Sign up to set email alerts
|

Short-term high salt intake reduces brachial artery and microvascular function in the absence of changes in blood pressure

Abstract: These data suggest that high salt intake reduces brachial artery endothelial function and switches the mediator of vasodilation in the microcirculation to a non-nitric oxide-dependent mechanism in healthy adults and acute exercise may switch the dilator mechanism back to nitric oxide during high salt diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 51 publications
0
43
0
2
Order By: Relevance
“…These studies are summarized in Table . The outcomes examined were diverse: one study assessed mortality outcomes (category I), two studies assessed morbidity outcomes (category II), two studies assessed outcomes related to symptoms/quality of life/functional status (category III), six studies assessed BP outcomes (category IV), seven studies assessed other clinically relevant surrogate outcomes (category V), and 10 studies assessed physiologic outcomes (category VI) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies are summarized in Table . The outcomes examined were diverse: one study assessed mortality outcomes (category I), two studies assessed morbidity outcomes (category II), two studies assessed outcomes related to symptoms/quality of life/functional status (category III), six studies assessed BP outcomes (category IV), seven studies assessed other clinically relevant surrogate outcomes (category V), and 10 studies assessed physiologic outcomes (category VI) …”
Section: Resultsmentioning
confidence: 99%
“…No primary research studies in the physiologic category (category VI) met the minimum methodological criteria. A range of outcomes were captured by the studies considered to be of lower quality, including all‐cause mortality, headaches/migranes, BP, cognitive function, acne, obesity and ghrelin, multiple sclerosis, BMD, gastric cancer, flow‐mediated dilatation, pulse wave velocity, markers of the renin‐angiotensin‐aldosterone system, heart rate, insulin resistance and the metabolic syndrome, brain tissue white matter hyperintensity, uric acid, and urinary albumin . Most of these studies found adverse effects of dietary salt on health, except for three that were neutral and one that found an inverse relationship between salt intake and headaches/migranes …”
Section: Resultsmentioning
confidence: 99%
“…Intravenous sodium loading may cause an acute increase in microvascular permeability in healthy male subjects, attributable to adverse effects on the endothelial surface layer . Even short‐term salt intake reduces brachial artery endothelial function and switches the mediator of vasodilation in the microcirculation to a non–nitric‐oxide dependent mechanism, even in healthy adults …”
Section: Microvascular Dysfunction Associated With High‐salt Intake Imentioning
confidence: 99%
“…31 Even short-term salt intake reduces brachial artery endothelial function and switches the mediator of vasodilation in the microcirculation to a non-nitric-oxide dependent mechanism, even in healthy adults. 32 Also the activity of the renin angiotensin system can be modified, since high-salt intake upregulates prorenin-receptor expression in the nephron, which seems to be involved in the regulation of renal dysfunction and proteinuria. 17 A high-salt intake has a negative influence on the homeostatic regulation of vascular bed in hypertensive patients, to a large degree via mechanisms that activate the local renin-angiotensin-aldosterone system in the vessels, 19 or via pathways that inhibit NO production.…”
Section: Crova Scul Ar Dys Fun C Ti On a Sso Ciated With Hi G H mentioning
confidence: 99%
“…Такой резуль тат может показаться неожиданным, но только на первый взгляд. Феномены сольчувствительности и сольрезистентности давно описаны у разных био логических видов -людей, шимпанзе и крыс [6,7]. При этом сольчувствительность (нарастание АД в ответ на повышение потребления хлорида натрия) и сольрезистентность могут встречаться как у нор мотоников, так и гипертоников.…”
Section: результаты исследования и их обсуждениеunclassified